Respuesta :

Answer:

D -2x+10

Step-by-step explanation:

-2(x-5)

Distribute the -2

-2*x -2*(-5)

-2x+10

Padoru

-2(x - 5)

This is the expression that we have to simplify to find an equivalent expression. In this problem, we can use the distributive property. In case you don't know, the distributive property states the following:

a(b + c) = ab + ac

Let's apply this to the expression.

-2(x - 5) = -2(x) - (-2)(5)

= -2x - (-10) = -2x + 10

This is answer choice D, which should be your answer.